Elementary surveying : instructional manual - La Putt, Juny Pilapil ([Place of publication not identifed] : [publisher not identified], 1981)
In this instructional manual the basic concepts of surveying are introduced, and features of different surveying instruments are discussed.
Part I. Surveying concepts: Field work; errors -- Part II. Measurement of distance -- Part III. Measurement of angles and directions -- Part IV. The engineer's transit -- Part V. Traversing -- Part VI. Traverse adjustment -- Part VII. Omitted measurements -- Part VIII. Area computations -- Part IX. Partitions -- Part X. Measurements of difference in elevation.
Keywords: SURVEYING